2011
DOI: 10.1108/02634501111138581
|View full text |Cite
|
Sign up to set email alerts
|

The key role of opportunism in business relationships

Abstract: PurposeThis study seeks to examine the key role of opportunism in business relationships relative to environment uncertainty (i.e. competitive intensity and market turbulence), bonding structure (i.e. specific assets and dependence), and relationship quality (i.e. trust and commitment).Design/methodology/approachInitially, informants were contacted by phone and a total of 581 surveys were mailed to small‐ and medium‐sized manufacturers asking them to answer questions about their suppliers. In total, 212 survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 56 publications
(105 reference statements)
2
54
1
3
Order By: Relevance
“…Technical readiness determines how capable a firm is to adopt an innovation (Iacovou et al, 1995;Kuan & Chau, 2001), but the technical complexities inherent in dynamic web technologies demand both technical skills and knowledge about the technology. Where these are lacking, managers may feel increasingly vulnerable to the possibility of being exploited (Mysen, Svensson & Payan, 2011), amplifying their perceptions of risk and therefore reducing their trust in adopting or using the technology (Pavlou, 2002;Pressey & Ashton, 2009). …”
Section: Technology Readinessmentioning
confidence: 99%
“…Technical readiness determines how capable a firm is to adopt an innovation (Iacovou et al, 1995;Kuan & Chau, 2001), but the technical complexities inherent in dynamic web technologies demand both technical skills and knowledge about the technology. Where these are lacking, managers may feel increasingly vulnerable to the possibility of being exploited (Mysen, Svensson & Payan, 2011), amplifying their perceptions of risk and therefore reducing their trust in adopting or using the technology (Pavlou, 2002;Pressey & Ashton, 2009). …”
Section: Technology Readinessmentioning
confidence: 99%
“…We took five items from Leonidou et al (2006) to measure uncertainty. Three items from Mysen et al (2011) served to measure specific assets. Of the RELQUAL focal constructs, we measured satisfaction with a three-item scale adapted from C. Lages et al (2005) and ; for commitment, we used a three-item scale adapted from C. Lages et al (2005); and to measure trust, we adapted a two-item scale from Ganesan (1994) and Zaheer, McEvily, and Perrone (1998).…”
Section: Methodsmentioning
confidence: 99%
“…As suggested by Kumar, Stern, andAnderson (1993, p. 1634), we used a key informant methodology and chose respondents "because they are supposedly knowledgeable about the issues being researched and able and willing to communicate about them." As suggested by Campbell (1955) and Mysen, Svensson, and Payan (2011), we checked the respondents' knowledge levels with two items: (a) "How much do you know about your firm's perspective on the study topics?" and (b) "How much do you know about specific experiences with importers?"…”
Section: Data Collection and Sample Descriptionmentioning
confidence: 99%
“…Even though this issue has been conceptualized slightly differently in the research, several empirical studies have confirmed the opportunism‐increasing effect of environmental uncertainty in exchange relationships (Katsikeas et al, ; Lai et al, ; Liu et al, ; Luo, ; Mysen et al, ; Skarmeas et al, ; Wang & Yang, ). Carson et al (), however, found that environmental uncertainty in contract R&D only unfolds its opportunism‐driving force under formal contract regimes but not under relational contract regimes.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…However, there is reason to assume the benefits of a refined explanation of opportunism that considers the specific features of a specific exchange situation. According to that view, some empirical studies have previously been conducted (e.g., Anderson (), Carson, Madhok, and Wu (); John (); Katsikeas, Skarmeas, & Bello, ; Lai, Tian, & Huo, ; Liu, Su, Li, & Liu, ; Luo, ; Mysen, Svensson, & Payan, ; Skarmeas, Katsikeas, & Schlegelmilch, ; Steinle, Schiele, & Ernst, ; Ting, Chen, & Bartholomew, ). However, as we will demonstrate, these studies show inconsistent results.…”
Section: Introductionmentioning
confidence: 99%